If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1b = nyb Reorder the terms: -1b + y = nyb Solving -1b + y = bny Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1bny' to each side of the equation. -1b + -1bny + y = bny + -1bny Combine like terms: bny + -1bny = 0 -1b + -1bny + y = 0 Add '-1y' to each side of the equation. -1b + -1bny + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 -1b + -1bny + 0 = 0 + -1y -1b + -1bny = 0 + -1y Remove the zero: -1b + -1bny = -1y Combine like terms: -1y + y = 0 -1b + -1bny + y = 0 The solution to this equation could not be determined.
| x^3y^2+5x^2y-14x=0 | | 5(x+4)+(3x-5)= | | 208=2(5z+2)+2(4z+3) | | 68=.2(20x+50)+2 | | y=-1.60x+b | | -9x^2+35x-30=1-x | | 4y-0.9=5y | | 9(x+5)=6x+2 | | (2+y)(3y+7)=0 | | -3(-5x+2)= | | (8x+1)2+5=10 | | 3x^4+33x^3+90x^2=0 | | -5(4x-2)= | | a^(1/3)*a^(4/3) | | 4x-7x-13=-3x+7-13 | | (6x+2)(3x-5)=(9x-4)(2x+4) | | p^2p/p^-5 | | 2/3x-1=-1/3x-5 | | (2x^4+6y)(2x^4-6y)= | | 2(3x+3)=5(x-4) | | -3(x+5)=2-2x | | 12x^2+4x+15=0 | | 3(7r-12)=21r-6 | | 63+30t+3t^2=0 | | 4x+2.9=9.7 | | 7(x+1)=-2(x-4)+x | | 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 |